Predictive value of bedside diaphragmatic ultrasonography for extubation success in critically ill patients after general anaesthesia: A meta-analysis with trial sequential analysis (TSA) - Lan Ma; Na Zhou; Kaiming Yuan; Zihao Xue; Kai Lv; Jingying Huang (Indian Journal of Anaesthesia)
Background and Aims: Accurate prediction of extubation success is crucial in critical care to avoid complications from premature or prolonged mechanical ventilation. Bedside diaphragmatic ultrasonography has emerged as a promising tool for assessing extubation readiness, but its effectiveness requires further validation. This meta-analysis evaluates the effectiveness of this method and uses trial sequential analysis (TSA) to assess evidence reliability and identify the need for further research. Methods: A comprehensive literature search was conducted across PubMed, Medline, Embase, Cochrane CENTRAL, Ovid, ISI Web of Science, and the Wanfang Database from 2014 to 2023. The included studies assessed diaphragmatic ultrasonography for predicting extubation success. Successful extubation is defined as maintaining spontaneous breathing for at least 48 hours post-extubation. Data extraction and quality assessment were performed using a random-effects model. Quality was assessed via the Newcastle-Ottawa Scale (NOS), and publication bias was evaluated through funnel plots and Egger’s test. Cumulative meta-analysis, sub-group analyses, and TSA were used to explore heterogeneity and assess evidence reliability. Results: Fourteen studies were included, demonstrating high quality. Diaphragm excursion (DE) and diaphragm thickening fraction (DTF) were significant predictors of extubation success. The diagnostic odds ratio (DOR) was 4.80 [95% confidence interval (CI): 3.86, 5.97)], with a sensitivity of 81.48% and a specificity of 86.86%. Significant heterogeneity was observed (I2 =85%, χ2 =87.19, P < 0.00001). TSA indicated that the cumulative evidence was insufficient. Conclusions: Diaphragmatic ultrasound, particularly DE and DTF, is useful for predicting extubation success, but current evidence is inconclusive. Further research is required to confirm these findings.